Application of the 3C Method to Study the Developmental Genes in Drosophila Larvae - Bylino, Oleg V.; Ibragimov, Airat N.; Digilio, Filomena Anna; Giordano, Ennio; Shidlovskii, Yulii V. (Frontiers in Genetics, 2022)
A transition from one developmental stage to another is accompanied by activation of developmental programs and corresponding gene ensembles. Changes in the spatial conformation of the corresponding loci are associated with this activation and can be investigated with the help of Chromosome Conformation Capture (3C) methodology. Application of 3C to specific developmental stages is a sophisticated task. Here we describe the use of the 3C method to study the spatial organization of developmental loci in Drosophila larvae. We critically analyze the existing protocols and offer our own solutions and the optimized protocol to overcome limitations. To demonstrate the efficiency of our procedure, we study the spatial organization of the developmental locus Dad in 3rd instar Drosophila larvae. Differences in locus conformation were found between embryonic cells and living wild-type larvae. We also observed the establishment of novel regulatory interactions in the presence of an adjacent transgene upon activation of its expression in larvae. Our work fills the gap in the application of the 3C method to Drosophila larvae and provides a useful guide for establishing 3C on an animal model.